Deep soil moisture limits the sustainable vegetation restoration in arid and semi-arid Loess Plateau - Li, Bin-Bin; Li, Pan-Pan; Zhang, Wan-Tao; Ji, Jing-Yi; Liu, Guo-Bin; Xu, Ming-Xiang (Geoderma, 2021)
•DSM in planted vegetation was lower than or approached the permanent wilting point.•Tree species, restoration age and precipitation had significant effects on DSM dynamics.•Platycladus orientalis and Hippophae rhamnoides showed advantages in keeping DSM.•Natural grassland was the best restoration way at precipitation less than 480 mm.•DSM limits the sustainability of vegetation restoration in the Loess Plateau. Deep soil moisture (DSM) (>100 cm) in water-limited regions usually functions as a soil reservoir and plays a vital role in plant productivity and ecosystem sustainability. However, the regional impacts of revegetation on the dynamics of DSM and the sustainability of restoration remain essentially unknown. This paper synthesized 94 peer-reviewed publications containing 5668 observations from 55 sites that focused on cropland, natural grassland, planted shrubs and planted forests on the Chinese Loess Plateau to identify the regional impacts of revegetation on the DSM under different restoration periods and precipitation gradients. The results showed the following: (1) Planted forests and shrubs exerted a strong negative impact on DSM within the 1000-cm depth in which the average soil moisture in 100–500 cm was lower than the average permanent wilting point (8.6%), the choice of tree species greatly influenced the DSM depletion extent, and Platycladus orientalis and Hippophae rhamnoides were recommended to maintain a better DSM condition. (2) The temporal pattern of DSM dynamics within the 1000-cm depth under planted forests and shrubs exhibited a significant and continuous decrease in first 20 years and remained relatively stable after 20 years, in which the soil moisture was lower than the average permanent wilting point, and grassland showed no obvious trends among different restoration periods (0–30 yr). (3) The limiting effects of precipitation changed greatly along the soil profile under planted forests and shrubs, and the restrictions may begin to appear when the mean annual precipitation is less than 480 mm when considering the deep soil layer (200–1000 cm). (4) The change rate of DSM within 1000 cm in planted forests (−0.08 to −0.11 g 100 g−1 yr−1) and planted shrubs (−0.05 to −0.20 g 100 g−1 yr−1) was much higher than that in natural grassland (−0.02 to −0.07 g 100 g−1 yr−1). Our results demonstrate that in arid and semiarid regions, the DSM in planted forests and shrubs was lower than or approached the average permanent wilting point and might limit the sustainability of vegetation restoration. When considering the joint effects between precipitation and vegetation type in deep soil layers, planted forests and shrubs are acceptable only when precipitation is greater than 480 mm, while grassland may be the best restoration type if precipitation is less than 480 mm.